The Quality of Methodological Reporting of Randomised Controlled Trial (RCT) Articles Published in Iranian and Top Nursing and Midwifery Journals Indexed in the Scopus Database using the CONSORT Checklist: A Cross-sectional Study - Bagherzadeh, Razieh; Jahanabad, Siavash Asadzadeh; Dehghani, Leila (Reviews on Recent Clinical Trials, 2025)
<span class=
Keywords: randomised controlled trial